Factors Contributing to increased cases of Peptic Ulcer Disease among Patients aged 18-70 years attending Kisoro Hospital Kisoro District. A Descriptive Cross-sectional Study. - Maniragaba, Nicholas; Atukuuma, Cliffe (Student's Journal of Health Research Africa, 2022)
Background: The purpose of the study was to determine factors contributing to increased cases of peptic ulcer disease among patients aged 18-70 years of attending Kisoro hospital Kisoro district. The study's specific objectives were to determine social-demographic, economic, and medical factors contributing to increased cases of peptic ulcer disease among patients aged between 18-70 years in Kisoro hospital Kisoro district. Methodology: A descriptive cross-sectional study design was used a study design; data was corrected on a sample of 60 respondents who were selected using a simple random sampling technique and questionnaires were used as data collection tools. Results: Regarding social-demographic factors contributing to increased cases of PUD, the majority (60%) of the respondents were older people aged between 41-70 years, most of the patients were males (60%) and most (50%) of the respondents were professionals. The study on economic factors contributing to increased cases of PUD revealed that most patients (75%) had a history of excessive alcohol consumption and the most (52%) of the respondents were low-income earners. Conclusion: From the study findings, social-demographic factors contributing to peptic ulcer disease were older people between 41 and 70 years. Recommendation: The researcher recommended the formulation and implementation of awareness programs and educative programs that would target peptic ulcer patients in hospitals and other people in the community especially men to increase awareness of the risk factors for PUD so that appropriate preventive measures are followed.